Papers of Robin Tait - Tait, Robin (R. M.) (1986)
Correspondence with Alec Bolton of Brindabella Press relating to eight books which he published and in which Tait Bindery was involved; binder's dummies; paper cuttings; copy of "A licence to print : Alec Bolton and the Brindabella Press" / Michael Richards and material relating to another book," Australia suite" / Lynn Hand which although planned as a Brindabella Press publication, was completed after Alec Bolton's death in 1996 and published by ETT Imprint.
Manuscript reference no. : NLA MS 9500.
National Library of Australia Manuscripts Section at MS 7426.
Bookbinder of Tait Bindery who worked with Alec Bolton on his Brindabella Press productions. Tait is also a conservator at the National Museum.
Keywords: Tait, Robin -- Correspondence; Tait, Robin -- Archives; Bolton, A. T., -- 1926-1996 -- Correspondence; Tait Bindery; Brindabella Press; Bookbinders -- Australia -- Archives; Bookbinders